Light-Induced Artemisinin Biosynthesis Is Regulated by the bZIP Transcription Factor AaHY5 in Artemisia annua. (10th May 2019) - Hao, Xiaolong; Zhong, Yijun; Ntzmann, Hans-Wilhelm; Fu, Xueqing; Yan, Tingxiang; Shen, Qian; Chen, Minghui; Ma, Yanan; Zhao, Jingya; Osbourn, Anne; Li, Ling; Tang, Kexuan
Abstract: Artemisinin, the frontline drug against malaria, is a sesquiterpenoid extracted from Artemisia annua . Light has been proposed to play an important role in the activation of artemisinin biosynthesis. Here, we report the basic leucine zipper transcription factor (TF) AaHY5 as a key regulator of light-induced biosynthesis of artemisinin. We show that AaHY5 transcription overlaps with that of artemisinin biosynthesis genes in response to light and in A. annua tissues. Analysis of AaHY5 overexpression and RNAi-suppression lines suggests that AaHY5 is a positive regulator of the expression of artemisinin biosynthesis genes and accumulation of artemisinin. We show that AaHY5 complements the hy5 mutant in Arabidopsis thaliana . Our data further suggest that AaHY5 interacts with AaCOP1, the ubiquitin E3 ligase CONSTITUTIVE PHOTOMORPHOGENIC1 in A. annua . In yeast one-hybrid and transient expression assays, we demonstrate that AaHY5 acts via the TF GLANDULAR TRICHOME-SPECIFIC WRKY 1 ( AaGSW1 ) in artemisinin regulation. In summary, we present a novel regulator of artemisinin gene expression and propose a model in which AaHY5 indirectly controls artemisinin production in response to changing light conditions.